2007
DOI: 10.1111/j.1467-2494.2007.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of serine protease activities in human stratum corneum and detection of a stratum corneum tryptase‐like enzyme

Abstract: Seasonal variation in stratum corneum (SC) biophysical and biological characteristics has been described previously. In particular, the winter season has been shown to affect more severely the properties of facial skin compared with forearm skin. Moreover, when compromised, such as in dry skin conditions, facial SC has been shown to contain increased inflammatory cytokines and proteases. Nevertheless, there have been no comparative studies of the activities and depth activity of several proteases in the SC on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
90
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 21 publications
12
90
1
Order By: Relevance
“…In addition, the face is one of the first body sites affected when atopic dermatitis (AD) develops and the ratio of fragile to mature corneocytes is higher here than on the inner upper arm (21). Voegeli et al (22) have also demonstrated higher levels of desquamation-related proteases on the face. All these features are found in AD and it was highlighted, therefore, that the forearm and forehead skin of healthy volunteers might model the distinction between a competent SC and one pre-predisposed to AD.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, the face is one of the first body sites affected when atopic dermatitis (AD) develops and the ratio of fragile to mature corneocytes is higher here than on the inner upper arm (21). Voegeli et al (22) have also demonstrated higher levels of desquamation-related proteases on the face. All these features are found in AD and it was highlighted, therefore, that the forearm and forehead skin of healthy volunteers might model the distinction between a competent SC and one pre-predisposed to AD.…”
Section: Introductionmentioning
confidence: 89%
“…Prior to tape-stripping the test sites were cleaned with cotton wool and water, and allowed to reacclimatize for 20 min. Extrapolation of depth reached by tape-stripping was based on the infrared absorbance (SquameScan 850A, CuDerm, Dallas, Tex., USA) of tape strips (to quantify protein) in accordance with published methodology [22,23]. …”
Section: Methodsmentioning
confidence: 99%
“…Assessment of protease activity was made on samples comprising 3 consecutive tape strips as previously described [22]. Caseinolytic, chymotrypsin-like and trypsin-like activities were determined using EnzCheck® (Life Technologies Ltd., Paisley, UK), MeOSuc-Arg-Pro-Tyr-AMC (Peptide Protein Research Ltd., Funtley, UK), and Boc-Phe-Ser-Arg-AMC (Bachem, Bubendorf, Switzerland) substrates, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Only KLK5, 8, and 14, however, are capable of degrading Dsg1 [72], but it is known that KLK8 also contributes to desquamation [73]. A depth activity profile of these enzymes are reported [74,66], but Voegeli et al [75] recently demonstrated that premature activation of, and elevated activity levels of KLK5, but not KLK7, on barriercompromised body sites such as the face but not the forearm ( > Fig. 7.7).…”
Section: Desquamationmentioning
confidence: 89%
“…There is a strong association of the . Figure 7.7 Protease activity (mean AE SEM) on tape-stripping pools of forearm and of cheek in function of depth of stratum corneum inhibitor-enzyme complexes at neutral pH, that is, as the SC is formed, and dissociation of the complexes occurs at low pH, within the outermost surface layers of the SC, where higher activities of the kallikreins are actually observed [75]. As at least pro-KLK7 is processed early in the formation of the SC and that LEKTI is secreted before the enzymes [78], presumably the inhibitors diffuse to the activated enzymes to control the later stages of desquamation.…”
Section: Desquamationmentioning
confidence: 96%